Cysteine, a facilitator of hypoxia adaptation and a promoter of drug-resistance : a new route to better diagnose and treat ovarian cancer patients - Nunes, Ana Sofia de Almeida da Costa (2019)
Ovarian cancer is the third most common gynaecologic malignancy and the main cause of death from gynaecologic cancer. Despite in the last 30 years an improvement of the overall survival of ovarian cancer patients has been observed, an increased cure rate was not registered. The high mortality associated with ovarian cancer is mainly due to a late diagnosis and resistance to treatment, barring ovarian cancer cure. Given the lack of a specific therapy against ovarian cancer, the treatment depends essentially on the use of generalised and comprehensive cytotoxic drugs, most of them belonging to the group of alkylating/oxidative agents, as platinum salts. Chemotherapy imposes high selection pressures in cancer cells, which may affect their evolutionary trajectories, selecting the chemoresistant ones, which will continue the progression and relapse of the disease, contributing to morbidity and mortality. In recent years, cancer metabolism has acquired a central position in oncobiology, being the metabolic remodelling a requirement for tumour progression, allowing cancer cells to respond to the selective Pressures of the microenvironment, such as hypoxia and cytotoxic drugs. These selective pressures promote cell death in non-adapted cells and positively select cells that exhibit growth advantage that will further sustain cancer progression and metastasis. Endogenous metabolism also limits drugs response. A role of cysteine in cancer by contributing for H2S generation and as a precursor of the antioxidant glutathione (GSH), were already reported. GSH has a crucial role as an antioxidant and also as a detoxifying system allowing the physiological maintenance of metabolic pathways, being intimately associated with chemoresistance. H2S is involved in several biological processes, acting also as an antioxidant and being associated with cancer progression and chemoresistance. As a solid tumour grows, such as an ovarian tumour, due to inefficient vascularisation, cancer cells are exposed to regions of hypoxia, known as a boost factor for tumour progression, metastasis and resistance to therapy. The present thesis aimed to clarify the relevance of cysteine metabolism in ovarian cancer cells adaptability to both hypoxia and platinum salts (carboplatin). These stressful conditions impose strong evolutionary selection pressure on cancer cells. Our results have provided evidence that cysteine metabolism has a role in ovarian cancer cells fast response and adaptation to hypoxic conditions that, in turn, are capable of driving chemoresistance. Moreover, cysteine showed to present a widespread protective effect against both hypoxia and carboplatininduced death among ovarian cancer cell lines. Importantly, our findings were also supported in a clinical context, as an overall increase of thiols concentration was found in serum from patients with ovarian neoplasms, regardless malignancy. Strikingly, the free levels of cysteine together with protein-Scysteinylation levels were able to distinguish patients with malignant tumours from patients with benign tumours and also from healthy individuals, supporting that the levels of cysteine and protein-S-cysteinylation can be putative biomarkers for ovarian cancer early diagnosis. Cysteine was also the prevalent thiol and Scysteinylation was the most abundant form of S-thiolated proteins in the ascitic fluid from patients with advanced disease. The ascitic fluid is an important compartment of the ovarian cancer cells microenvironment, supporting a clinical relevance of cysteine also in the progression of the disease. Given the protective effect of cysteine in hypoxic ovarian cancer cells, we also aimed to address the possible mechanisms by which cysteine would be beneficial under hypoxia. Our results have supported a role of a higher thiols turnover in the adaptation to this environment, especially in ES2 cells. Moreover, results have also supported a role of cysteine in energy production mediated by the xc- system, that requires cysteine metabolism instead of H2S per se. However, the direct role of cysteine in ATP production is still uncertain as this amino acid can have an indirect contribution to ATP synthesis driven by an increased GSH content, allowing the redox equilibrium crucial for the overall cellular metabolism. Strikingly, 1H-NMR results have suggested that cysteine impacted profoundly ES2 cells metabolism under hypoxia, allowing a metabolic reprogramming, that probably underlies ES2 cells adaptation to hypoxia. Taken together, this thesis has shed light on new paths for ovarian cancer screening, diagnosis, prognosis and therapy, where cysteine metabolic profile might allow the design of new and useful approaches to fight this disease, thus overcoming its poor prognosis.